KETIDAKWAJARAN SKOR BERDASARKAN TEORI RESPONSI BUTIR - BUDI SANTOSO (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2011)
The objective of this research is to compare inappropriateness based on Item response theory as an effect of using model of scoring and number of options for multiple choice items. The research method used quasi experiment. Independent variable of this research are Correct Score (CS), punishment score (PS), and Reward Score (RS). And also three and five option multiple choice items. To see this comparison, the proportions of fair score are compared by using gZ index. For the student corrected by CS model compared between the group who answer three choice item and group who answer five choice item. While for group of student doing test with a five choice item compared between the couple of CS, PS and RS. The result of this research indicate that for low ability (q <- 1) student, the use of CS model for student who answer a five choice item compared has more fair score than students who answer a three choice item. But for high ability (q > 1) students there are no difference fair score among the two groups. For the students who answer a five choice item, indicate that for high ability student, the use of PS and RS model have more fair score compare with CS model, but for PS model does not yield fair score difference compare with RS model. Meanwhile for low ability student there is no difference in fair score among the use of three models of scoring.